Image-based Modeling of Haussmannian Facades - Liu, Chun; Gagalowicz, André (International Journal of Virtual Reality, 2010)
This paper describes techniques and algorithms for Haussmannian facade modeling. Although buildings are complex artificial objects which are difficult to interpret, Haussmannian buildings carry a more consistent typology and composition rhythm. By incorporating the architectural knowledge of the Haussmannian facade into an image analysis process, facade structure information can be automatically inferred. Moreover, in order to further refine the facade analysis, an image synthesis process is integrated and a feedback loop is created for producing more stable results. With this methodology, a solid technique and process for image-based modeling of Haussmannian or similar building facades have been established.